2003
DOI: 10.1590/s1517-74912003000400004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effect of a herbal dentifrice on the control of plaque and gingivitis: a double-blind study

Abstract: The aim of this randomized, double-blind clinical trial was to evaluate the effect of the Paradontax dentifrice on the reduction of plaque and gingivitis. Subjects were randomly allocated into either the test group (n = 15, Paradontax) or the control group (n = 15, standard dentifrice with fluoride). Plaque levels were measured using the Turesky modification of the Quigley & Hein Plaque Index (PI), and gingivitis was evaluated with the Gingival Index (GI). Subjects were asked to brush their teeth with the allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1
12

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 13 publications
3
63
1
12
Order By: Relevance
“…The viability of volunteer plaque bacteria reportedly decreased following exposure to PF, although effects were moderate compared to those of the nonherbal, triclosan formulation (37). No significant differences in plaque and gingival inflammation scores were reported in a previous investigation when PF was compared to a fluoride-containing toothpaste in a 21-day clinical trial (38). Compared to treatment with a fluoride toothpaste, treatment with PF reportedly reduced plaque accumulation and gingival inflammation scores among patients with chronic gingivitis (39).…”
Section: Discussionmentioning
confidence: 78%
“…The viability of volunteer plaque bacteria reportedly decreased following exposure to PF, although effects were moderate compared to those of the nonherbal, triclosan formulation (37). No significant differences in plaque and gingival inflammation scores were reported in a previous investigation when PF was compared to a fluoride-containing toothpaste in a 21-day clinical trial (38). Compared to treatment with a fluoride toothpaste, treatment with PF reportedly reduced plaque accumulation and gingival inflammation scores among patients with chronic gingivitis (39).…”
Section: Discussionmentioning
confidence: 78%
“…It is important that clinical tri- als verify the efficacy of any new product, instead of simply assuming that the product is efficient based on laboratory studies. In a previous study 18 , Parodontax  was unable to promote a significant reduction in PI and GI when compared to a standard dentifrice containing only fluoride. One possible reason for the conflicting results obtained by either study is the population participating in each study.…”
Section: Discussionmentioning
confidence: 79%
“…Some studies have reported that Parodontax  is able to significantly decrease plaque and gingivitis 24,25 , while other publications showed no effectiveness of the dentifrice when compared to a control 16,18,20 . In many trials, study subjects receive dental prophylaxis and oral hygiene instructions prior to the commencement of the experiment.…”
Section: Introductionmentioning
confidence: 99%
“…However, many other studies were carried out regarding the effect of toothpaste containing other chemical adjunct on their effect on the plaque formation. The study on tooth paste and extract containing herbal, [10][11][12][13] amine fluorides, 14 sodium fluoride or stannous fluoride 15 and triclosan 16,17 were failed to prove the superiority of the tested toothpaste as compared to the control. On the other hand, there were also studies indicated the toothpaste containing stannous fluoride, 18 salivary substitutes 19 and chlorhexidine mouth rinses 20 had better prevention in the plaque formation in comparison to the control materials.…”
Section: Resultsmentioning
confidence: 99%